x/ay/b=ab ax+by=a3+b3 slove by elimination method
Question
2 Answer

1. User Answers MaheswariS
Answer:
solution is
[tex]x=a^2[/tex] and [tex]y=b^2[/tex]
Stepbystep explanation:
The given equations can be written as
[tex]bxay=(ab)ab[/tex]..............(1)
[tex]ax+by=a^3+b^3[/tex]............(2)
[tex](1)*b\implies\:b^2xaby=(ab)ab^2[/tex]
[tex](2)*a\implies\:a^2x+aby=a(a^3+b^3)[/tex]
Adding we get
[tex](a^2+b^2)x=a^2b^2ab^3+a^4+ab^3[/tex]
[tex](a^2+b^2)x=a^2b^2+a^4[/tex]
[tex](a^2+b^2)x=a^2(a^2+b^2)[/tex]
[tex]x=a^2[/tex]
put [tex]x=a^2[/tex] in (2)
[tex]a(a^2)+by=a^3+b^3[/tex]
[tex]a^3+by=a^3+b^3[/tex]
[tex]by=b^3[/tex]
[tex]y=b^2[/tex]
solution is
[tex]x=a^2[/tex] and [tex]y=b^2[/tex]

2. User Answers perfectfitnessnutrit
Stepbystep explanation:
The given equations can be written as
bxay=(ab)abbx−ay=(a−b)ab ..............(1)
ax+by=a^3+b^3ax+by=a
3
+b
3
............(2)
(1)*b\implies\:b^2xaby=(ab)ab^2(1)∗b⟹b
2
x−aby=(a−b)ab
2
(2)*a\implies\:a^2x+aby=a(a^3+b^3)(2)∗a⟹a
2
x+aby=a(a
3
+b
3
)
Adding we get
(a^2+b^2)x=a^2b^2ab^3+a^4+ab^3(a
2
+b
2
)x=a
2
b
2
−ab
3
+a
4
+ab
3
(a^2+b^2)x=a^2b^2+a^4(a
2
+b
2
)x=a
2
b
2
+a
4
(a^2+b^2)x=a^2(a^2+b^2)(a
2
+b
2
)x=a
2
(a
2
+b
2
)
x=a^2x=a
2
put x=a^2x=a
2
in (2)
a(a^2)+by=a^3+b^3a(a
2
)+by=a
3
+b
3
a^3+by=a^3+b^3a
3
+by=a
3
+b
3
by=b^3by=b
3
y=b^2y=b
2
solution is
x=a^2x=a
2
and y=b^2y=b
2